2018
DOI: 10.1177/1076029618785771
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between CHA2DS2-VASc Score and Right Ventricular Dysfunction in Patients With Acute Pulmonary Thromboembolism

Abstract: In this study, the association between the right ventricular dysfunction (RVD) and CHA2DS2-VASc (C: congestive heart failure or left ventricular systolic dysfunction, H: hypertension, A: age of ≥ 75 years, D: diabetes mellitus, S: previous stroke, V: vascular disease, A: age between 65 and 74 years, Sc: female gender) scores was investigated in patients with acute pulmonary thromboembolism (PTE). The patients have been assigned to 3 subgroups as massive, submassive, and nonmassive PTE. The CHA2DS2-VASc scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 27 publications
(29 reference statements)
3
12
0
Order By: Relevance
“…Age is an obvious risk factor for patients with CAD and AF (31,33), and elderly individuals are more likely to have coexisting CAD and AF, thus the risk of death in elderly patients with CAD and AF is higher. In addition to the assessment of thromboembolic risk in patients with AF, the CHA 2 DS 2 -VASc score has been shown to predict the adverse outcomes for other cardiovascular conditions, such as chest pain (25), ACS (21,22), AMI (24), HF (20), pulmonary emboli (23), and ACS undergoing percutaneous coronary intervention (PCI) (26). Therefore, we believe that the CHA 2 DS 2 -VASc score is a feasible predictor of prognosis in elderly patients with CAD and AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age is an obvious risk factor for patients with CAD and AF (31,33), and elderly individuals are more likely to have coexisting CAD and AF, thus the risk of death in elderly patients with CAD and AF is higher. In addition to the assessment of thromboembolic risk in patients with AF, the CHA 2 DS 2 -VASc score has been shown to predict the adverse outcomes for other cardiovascular conditions, such as chest pain (25), ACS (21,22), AMI (24), HF (20), pulmonary emboli (23), and ACS undergoing percutaneous coronary intervention (PCI) (26). Therefore, we believe that the CHA 2 DS 2 -VASc score is a feasible predictor of prognosis in elderly patients with CAD and AF.…”
Section: Discussionmentioning
confidence: 99%
“…The CHA 2 DS 2 -VASc score [congestive heart failure, hypertension, age ≥75 years (doubled), diabetes, stroke/transient ischemic attack/thromboembolism (doubled), vascular disease (prior myocardial infarction, peripheral artery disease, or aortic plaque), age 65-74 years, sex category (female)] has been used for the assessment of thromboembolic (TE) risk and the guidance of antithrombotic treatment in patients with AF (20). In addition, this simple and well-established scoring system has been shown to predict the risk for other conditions beyond its original designations (20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the advances in medical therapies, APE is still a major cause of morbidity and mortality worldwide. Previously, several studies revealed that patient-related clinical factors-such as advanced age and hypotension 2,14 or other some laboratory biomarkers-such as brain-type natriuretic peptide, creatinine kinase-myocardial band and high sensitive troponin I, etc-were found to be useful for the prediction of early mortality in patients with APE. 5,6 The plasma osmolality is a combination of sodium, plasma glucose and BUN.…”
Section: Discussionmentioning
confidence: 99%
“…The components of these two scores are associated with atherosclerosis, vascular spasm, and microvascular dysfunction, which overlap the risk factors of NRP [7]. Several recent studies have also shown that the CHA 2 DS 2 -VASc scores are associated with the severity of coronary artery disease, its prognosis, and NRP in patients with acute MI, contrast-induced nephropathy after PPCI for acute coronary syndrome, in-stent restenosis, acute stent thrombosis, mechanical mitral valve thrombosis, and right ventricular dysfunction [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 96%